Pseudoamblyopia in Congenital Cyclotropia. (26th July 2017) - Frattolillo, Antonio; Tassi, Filippo; Di Croce, Valentina; Schiavi, Costantino
Abstract : Purpose . To study the effect of surgery on amblyopia and suppression associated with congenital cyclovertical strabismus. Methods . The fixation pattern was investigated with microperimetry before and soon after surgery in ten consecutive children operated for congenital superior oblique palsy at the S. Martino Hospital, Belluno, Italy, between September 2014 and December 2015. Changes in visual performance in terms of best-corrected visual acuity (BCVA) and stereopsis between the day before and one week after surgery were also evaluated. No other amblyopia treatment has been administered during the time study. Results . Surgical correction of the excyclodeviation in congenital SO palsy determined monocular and binocular sensory consequences: monocularly, in the cyclodeviated amblyopic eye, BCVA (0.46–0.03 LogMAR; p < 0.0001 ) and the fixation pattern improved, as demonstrated by microperimetry examination. Binocularly, stereopsis improved or emerged while suppression at the Worth four-dot test disappeared. Conclusions . In the absence of further amblyopic factors such as coexisting constant vertical and/or horizontal deviation and anisometropia, the amblyopia encountered in congenital SO palsy may resolve soon after the surgical alignment. Therefore, it may be considered and defined "pseudoamblyopia."